Detection of vertical root fractures in the presence of artefacts by digital radiography and cone beam computed tomography (Research, Society and Development, 2021)
The correct diagnosis of vertical root fractures (VRF) in the presence of artifacts is a challenge for clinicians and endodontists. Moreover, there is controversy about which imaging technique is best for this purpose. In an in vitro model, we evaluated the diagnosis of VRF in teeth treated endodontically with and without intraradicular metal posts, using the Clark technique and cone beam computed tomography (CBCT), as well as the interference of artifacts with the diagnosis. Twenty-two first or second maxillary or mandibular premolars were included. Teeth were randomly allocated to three groups: G1 (two teeth without fracture with endodontic treatment and one with an intraradicular metal post); G2 (10 fractured teeth with endodontic treatment); and G3 (10 fractured teeth with endodontic treatment plus a metal post). The examiners recorded the presence or absence of fracture and its location and classified its type. There was no statistically significant difference between image acquisition systems. When differentiating the teeth (first vs. second premolars), there was a statistically significant difference among the examiners (p=0.020). However, when comparing the values obtained by the examiners regarding the visualization of the fracture site as well as the presence of fracture correlated with the presence of a metal post and angulation, there were no statistically significant differences (p>0.05). Digital radiographs and CBCT were similar for the diagnosis of VRF. High sensitivity was observed by CBCT image reconstructions. Therefore, the presence of metal posts generated artifacts, resulting in low sensitivity, specificity and accuracy.